2016
DOI: 10.5762/kais.2016.17.12.316
|View full text |Cite
|
Sign up to set email alerts
|

Development of Postoperative Self Care Mobile App for Kidney Transplantation Patients

Abstract: The purpose of this research was to develop a self-care application for kidney transplantation patients based on a review of previous literatures and the results of a survey that evaluated the needs of patients. The research proceeded in ADDIE order of analysis, design, development, implementation, and evaluation stages. In the analysis phase, interviews were conducted on over 5 kidney transplantation patients. Moreover, related applications and literatures were reviewed to develop application contents. App-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Malnutrition has been reported to increase mortality rates 24 and thus, nutrition management is important in the rehabilitation of frail older adults after osteoporotic hip fracture. 25 However, nutrition management was addressed in some mobile applications for patient with colorectal cancer 26 or kidney transplantation, 27 but not for those with hip fracture surgery. Thus, we believe that our study to develop the mobile application and validate it might be meaningful to improve rehabilitation in older adults after hip fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malnutrition has been reported to increase mortality rates 24 and thus, nutrition management is important in the rehabilitation of frail older adults after osteoporotic hip fracture. 25 However, nutrition management was addressed in some mobile applications for patient with colorectal cancer 26 or kidney transplantation, 27 but not for those with hip fracture surgery. Thus, we believe that our study to develop the mobile application and validate it might be meaningful to improve rehabilitation in older adults after hip fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
“…16 Meanwhile, the visual components in the design suitability scored the lowest at 1.88 and was comparable to the results of post-operative self-care application evaluation for those after kidney transplantation. 27 The visual components in the design suitability were connected with a comment from experts that the yellow letters on a black background were difficult to read despite the significant difference in color and brightness. 29 A study found that bright letters on a dark background facilitated readability for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The developed mobile application was used by experts and users from May 22 to 26, 2021. The number of participants in this study was determined by referring to the sample size of a previous study [ 22 ], in which experts and user groups evaluated a developed mobile application. The expert group consisted of eight experts, including three professors specializing in pediatric nursing with NICU clinical experience, a registered nurse with more than 20 years of NICU work experience, a professor specializing in pediatric care for high-risk neonates, a professor of occupational therapy specializing in child development, and two mobile application-related programmers.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, eHealth interventions have been implemented to improve medication adherence or knowledge by organ transplant and other patients [15][16][17][18][19][20][21][22][23]. Further, previous research has reported that patients with organ transplants are an ideal population for utilizing eHealth tools, such as mobile apps [15].…”
Section: Introductionmentioning
confidence: 99%
“…The information provided can offer health education; monitor, record, and transmit data about health behaviors and indicators, such as blood pressure or blood sugar levels; and give reminders, feedback, and counseling to patients through methods such as mobile apps, the Internet, and electronic devices [16,17]. Studies applying various eHealth interventions for improving medication adherence by organ transplant patients have been published, including research on developing mobile apps for kidney transplant patients [18] and methods used to monitor mobile phones, computers, or reminder systems in connection with transplant patients [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%